DD-006 Prescriptions and equipment for unit dose capecitabine in Oncology Pharmacy Laboratory – Ausl Bologna – Italy. (24th February 2014) - Cesari, R; Santilli, G; Scarlattei, D; Marotta, M; Borsari, M
Abstract : Background: Since December 2012, the Oncology Pharmacy Laboratory of AUSL Bologna has been preparing and delivering patient unit doses of capecitabine. In order to ensure greater patient safety and better management of the drug in terms of traceability of prescription, preparation and dispensing, the path has been set in accordance with Recommendations 7 and 14 of the Ministry of Health and in accordance with Medicinal Products GMP (FU XII Ed). Purpose: To evaluate clinical appropriateness, adherence to home treatment and to perform an economic analysis related to the unit dose equipment. Materials and methods: The laboratory uses software that allows the prescription to be traced by the clinical oncologist, validation and staging by the pharmacist and the drug to be dispensed to the patient. This software processed and subsequently analysed data from prescribed capecitabine treatments delivered in January–May 2012 in original packs compared to the same period of 2013 supplied in customised unit doses. Results: Analysis of the data showed that in January–May 2013 compared to January–May 2012, the overall number of patients treated with capecitabine increased by 32% (108 vs. 81), related to an increase in the number of prescriptions of 28% (345 vs. 270). Under Law 648/9, the Italian Ministry of Health extends the clinical indication of use for some drugs. In 2013 the use of capecitabine was extended to locally advanced or metastatic breast cancer in combination with other anticancer drugs. The number of patients prescribed capecitabine under indication L648/96 fell by 16%, while patient adherence to the treatment increased by 5%. Regarding other allowed clinical indications, an assessment of tumour sites found in 2013 a reduction of 15.1% in patients treated with capecitabine for carcinoma of the colon and an increase of 16.4% in patients with breast cancer in monotherapy. Finally, it was seen that despite an increase in the number of patients treated, preparing unit doses of capecitabine in 2013 resulted in a saving in terms of reducing wasted tablets of 2, 355, representing a reduction in expenditure of 19.6%, only for the patients who completed treatment within the period considered. Conclusions: Analysis of the data shows that the computerisation of unit doses of capecitabine carried out in 2013 enabled us to work in a regime of greater patient safety due to traceability of system information and batch expiry of the drug, while precise control of treatment generated net cost savings compared with original pack dispensing in 2012. No conflict of interest.